استئجار الاصول الثابتة - غباشي, محمد (Dirasat in Economics and Business, 1968)
The following a bstracts are short synopses of articles appearing in the Arabic part of the Review.They are summarized here for the benefit of those whocannot read Arabic. In a like manner, each major English or French article is presented as a short resume in the Arabic section.